The House of Tiny Tearaways - Byron, Tanya Dr. (London BBC, 2005)
Dr Tanya Byron encourages parents to understand the roots of the parenting issues they are facing, recognise where and why the problems exist and outlines how to implement practical solutions within their families to turn destructive behaviour patterns into positive ones.
Includes Illustrations and index.
Keywords: Behavior modification